Naturalizing Africa : ecological violence, agency, and postcolonial resistance in African literature - Iheka, Cajetan Nwabueze (Cambridge, United Kingdom ; New York, NY, USA : Cambridge University Press, 2018)
"The book makes four interventions: (1) it extends the domain of African literary studies from one primarily focused on humans to one that explores the complexities of human-nonhuman relations in the different sites under consideration; (2) it rethinks the dominant notion of agency based on intentionality and proposes ways of conceiving distributed agency or varieties of agency functioning between human beings and other environmental actors; (3) it broadens our perspective on violent resistance and its complicity in ecological degradation, thus reopening the question of violence that earlier marked the struggle for liberation by such figures as Frantz Fanon; and (4) it contributes to the larger project of envisioning alternative, sustainable ecosystems."--Publisher's summary.
Introduction : naturalizing Africa -- African literature and the aesthetics of proximity -- Beyond human agency : Nuruddin Farah and Somalia's ecologies of war -- Rethinking postcolonial resistance : the Niger Delta example -- Resistance from the ground : agriculture, gender, and manual labor -- Epilogue : rehabilitating the human.
Includes bibliographical references (pages 167-206) and index.
Catalography
Keywords: Ecocriticism; Ecocriticism in literature; Postcolonialism in literature; Human-animal relationships -- Africa; Human-plant relationships -- Africa; Human beings -- Effect of environment on -- Africa; Nature -- Effect of human beings on -- Africa; Human ecology -- Africa; Human ecology in literature; Violence -- Environmental aspects -- Africa; War -- Environmental aspects -- Africa